Particularities and Clinical Applicability of Saccharin Transit Time Test - Rodrigues, Fernanda [UNESP]; Freire, Ana Paula [UNESP]; Uzeloto, Juliana [UNESP]; Xavier, Rafaella [UNESP]; Ito, Juliana [UNESP]; Rocha, Marceli [UNESP]; Calciolari, Renata [UNESP]; Ramos, Dionei [UNESP]; Ramos, Ercy [UNESP] (Georg Thieme Verlag Kg, 2019)
Introduction The importance of mucociliary clearance (MCC) for the respiratory system homeostasis is clear. Therefore, evaluating this defense mechanism is fundamental in scientific research and in the clinical practice of pulmonology and of associated areas. However, MCC evaluation has not been so usual due to the complexity of methods that use radiolabeled particles. Nevertheless, as an interesting alternative, there is the saccharin transit time (STT) test. This method is reproducible, simple to perform, noninvasive, does not demand high costs, and has been widely used in studies of nasal MCC. Although the STT test is widely used, there is still lack of a detailed description of its realization. Objective The present literature review aims to provide basic information related to the SIT test and to present the findings of the previous studies that used this method, discussing variations in its execution, possible influences on the obtained results and limitations of the method, as well as to relate our experience with the use of STT in researches. Data Synthesis There are several factors that can alter the results obtained from STT tests, which would raise difficulties with proper interpretation and with the discussion of the results among different studies. Conclusions Saccharin transit time is a widely used method for the evaluation of nasal MCC, and therefore, the standardization related to the previous and concurrent to test orientations, and also its execution, become essential to improve its accuracy, and allow comparisons among different studies.
Keywords: mucociliary clearance; airway management; mucus